O regime jurídico do ICMS incidente sobre a prestação de serviços de transporte interestadual e intermunicipal na constituição federal de 1988 - Galvão, Flávio Alberto Gonçalves (2008)
The objective of this thesis is to present the constitutional and judicial rationale of the hypothesis of incidence of the mandatory tax when it comes to transportation services as a result of the incidence of the intermunicipal and interstate tax of circulation of goods and transportation services mentioned on the article 155, II, of the 1998 Federal Constitution. After nineteen years of implementation of the 1988 Constitution, judicial works on the hypothesis of incidence of the Imposto sobre Circulação de Mercadorias e Prestação de Serviços (ICMS), ¨tax on the circulation of goods and services,¨ on operations of circulation of goods are abundant, however, when it comes to intermunicipal and interstate transportation, matters which are related to the constitutions of each member state in agreement with other services taxed by the cities, and the analysis of various types of transportation, including the constitutional regime of international transportation, present unclear and troublesome definitions with doctrinal problems. The methodology used comes from the historical interpretation present in the first section of the work to reveal the changes with time of the application of the constitutional and below-constitution tax laws on transportation services, and starting from the 1998 Constitution, the judicial interpretation is based upon the logical and juridical method of the constitutional norms in its syntactic and semantic aspects in accordance with the system of constitutional tax principles. The results found identify the elements of the general rule of incidence of the ICMS applied to the interstate and intermunicipal transportation services regarding the article 155, II, of the 1988 Federal Constitution, based on the conduct and delimitation of the constitutional competencies, with the identification of the types of transportation subject to taxation, non-incidence, immunity, taxpayer and non-taxpayer, time and space related aspects, possible calculation basis and possible tax rates